(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article examines the nature and essence of the concept of “system”. A new law of inextricable connection between the material and immaterial duality of systems is established. It is emphasized that this law operates in all spheres: physical, biological and social systems. It belongs to the category of universal laws of nature